Risk, Incidence, and Mortality of Breast Cancer in Primary Sjögren’s Syndrome: A Systematic Review and Meta-Analysis - Deng, Jian; Liu, Mengsi; Xiao, Ruoyi; Wang, Jin; Liao, Xibei; Ye, Zhen; Sun, Zhen (Frontiers in Immunology, 2022)
Background: We conducted a systematic review and meta-analysis to investigate the risk, incidence, and mortality of breast cancer in patients with primary Sjögren's syndrome (pSS). Methods: We systematically searched Embase, PubMed, and Web of Science on January 31, 2022 to identify the study that assessed risk, incidence, and mortality of breast cancer in pSS. We calculated the pooled effect estimates by using a fixed or random-effects model based on heterogeneity test. Results: Ten studies involving 725,805 participants and 65,023 pSS patients were included in our analysis. The pooled result showed that, overall, pSS was not associated with the risk (SIR=0.92, 95%CI: 0.66-1.29, P=0.646) and mortality (HR = 0.78, 95%CI: 0.26-2.34, P = 0.664) of breast cancer; however, when stratified by geographic region, we found that patients with pSS in Asian countries (SIR=1.32, 95%CI: 1.10-1.58, P=0.003) and Argentina (SIR=3.76, 95%CI: 1.04-9.45, P=0.019) had an elevated risk of breast cancer, while pSS in Europe was associated with a reduced risk (SIR=0.61, 95%CI: 0.51-0.73, P<0.001). The pooled result from 28,635 female pSS patients indicated that the incidence of breast cancer was 2.15 (95% CI: 1.33-3.50) per 1000 person/years. Conclusion: This study suggests that there may be geographical differences in the association between pSS and breast cancer risk; patients with pSS in European countries are associated with a lower risk of breast cancer, while Asia and Argentina are the opposite. Future research is needed to further characterize the effect of pSS on breast cancer risk and the pathophysiological mechanisms underlying this association to unravel the complex relationship between the two.